DESKRIPSI MISKONSEPSI SISWA PADA MATERI GERAK LURUS DI SMA NEGERI 1 SUNGAI RAYA - Linawati, Linawati; Maria Silitonga, Haratua Tiur; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe study investigated student misconception and cause of the misconception on straight motion. A descriptive survey was employed. The sample for the study was 87 students of X grade from SMA Negeri 1 Sungai Raya. Data are collected by using multiple choice diagnostic tests with open reason and interview. The result indicated that student made .66% misconception about straight motion. The misconceptions were on the eleven concept, including: the sama distance as displacement (32.18%), in parallel positions two objects have the same speed (35.63%), objects in front of other objects moving with greater velocity (20, 63%), if speed increases, then acceleration is more and more (72.99%), the downward trajectory is a slowing down trajectory (16.1%), the acceleration of the object when it stops is zero (86.21%), if the object velocity is zero, then the acceleration is also zero (34.48%), objects with a larger mass will fall faster than objects with lighter mass (94.25%), the higher the object, the smaller the acceleration, and vice versa (83,36%), an object thrown up has zero acceleration at the highest point (88.50%) and, the direction of acceleration is always the same as the velocity (85.06%). Keywoards: Misconception, straight motion, diagnostic tests